2017
DOI: 10.1038/ijo.2017.90
|View full text |Cite
|
Sign up to set email alerts
|

Grape seed proanthocyanidin supplementation reduces adipocyte size and increases adipocyte number in obese rats

Abstract: A Pascual-Serrano, A Arola-Arnal, S Suárez-García, FI Bravo, M Suárez, L Arola and C Bladé OBJECTIVES: White adipose tissue (WAT) expands through hypertrophy (increased adipocyte size) and/or hyperplasia (increased adipocyte number). Hypertrophy has been associated with insulin resistance and dyslipidemia independently of body composition and fat distribution. In contrast, hyperplasia protects against metabolic alterations. Proanthocyanidins, which are the most abundant flavonoids in the human diet, improve me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 44 publications
(45 reference statements)
2
49
1
Order By: Relevance
“…The images obtained by micro‐CT scanning also revealed less visceral fat (darker grey regions in the image) in the HP400 group compared to HC group, as shown in Figure (D), confirming the effect of PE. Adipocyte size is known to be an independent predictor of metabolic diseases, and adipocyte hypertrophy has been associated with insulin resistance and dyslipidemia (Pascual‐Serrano et al., ). Histological analysis revealed that PE supplementation reduced adipocyte hypertrophy and these results were in accordance with the serum leptin and adiponectin levels (Cui et al., ; Skurk, Alberti‐Huber, Herder, & Hauner, ).…”
Section: Resultsmentioning
confidence: 99%
“…The images obtained by micro‐CT scanning also revealed less visceral fat (darker grey regions in the image) in the HP400 group compared to HC group, as shown in Figure (D), confirming the effect of PE. Adipocyte size is known to be an independent predictor of metabolic diseases, and adipocyte hypertrophy has been associated with insulin resistance and dyslipidemia (Pascual‐Serrano et al., ). Histological analysis revealed that PE supplementation reduced adipocyte hypertrophy and these results were in accordance with the serum leptin and adiponectin levels (Cui et al., ; Skurk, Alberti‐Huber, Herder, & Hauner, ).…”
Section: Resultsmentioning
confidence: 99%
“…The disadvantage is that gavage requires a large amount of prior preparation, and gavage may increase the risk of death of the animal during administration. Previous studies have reported that for HFD‐induced obese mice, the dose of GSPE range from 25 to 300 mg/kg/day, and the treatment duration range from 7 to 13 weeks (Baiges et al, ; Liu et al, ; Pascual‐Serrano et al, ). In the preliminary experiment, we tested five different doses (25, 50, 100, 200, and 300 mg/kg/day) and found that only the 200 mg and 300 mg groups had significantly lower body weight than the control group at 7 weeks (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Compared to small adipocytes, hypertrophic adipocytes are more likely to attract inflammatory cells, have more fat-soluble and insulin resistance effects, resulting in metabolic disorders. However, proliferation can prevent metabolic changes [42]. GSPE supplementation can regulate WAT in visceral and subcutaneous tissues, reduce adipocyte hypertrophy and increase adipocyte proliferation, thus improving WAT function.…”
Section: Regulating the Function Of White Adipose Tissue And Brown Admentioning
confidence: 99%